Effect of Crocin on Spermatogenesis in Streptozotocin-induced Diabetic Rats - Mohammad Ehsan Bayatpoor; Saeed Mirzaee; Mohammad Taghi Mohammadi (Journal of Mazandaran University of Medical Sciences, 2018)
Background and purpose: Diabetes mellitus affects male reproductive functions at multiple levels such as spermatogenesis, steroidogenesis, and sexual behaviors. The pleotropic protective roles of crocin in different pathological states have been reported, so, this study aimed at examining the protective effects of crocin on spermatogenesis in experimentally-induced diabetes in rats. Materials and methods: In an experimental study, 18 male Wistar rats were randomly divided into three groups; normal, diabetic, and crocin-treated diabetic groups. Diabetes was induced using i.v. injection of streptozotocin (40 mg/kg) and treatment group received i.p. injection of crocin (20 mg/kg/day) for 60 days. At the end of the test, we studied blood glucose level, sperm count, and testis weight, and histopathological assessment was also performed. Results: Induction of diabetes enhanced blood glucose levels in diabetic group (229±11mg/dL) whereas crocin significantly decreased blood glucose levels of treated diabetic group (118±4mg/dL) compared with the diabetic group (P=0.001). Sperm number decreased considerably in diabetic group (19.4±24 million/mL vs. 4.4±10 million/mL) but crocin significantly increased that (10.3±14 million/mL), (P=0.037). Diabetes also developed histopathological changes in seminiferous tubules and led to reduction of testis weight in diabetic rats, whereas crocin diminished these damages. Conclusion: Our findings revealed that crocin could protect male reproductive organ against diabetes and improve spermatogenesis in experimentally-induced diabetes in rat.